Eine Evaluierung der Akzeptanz von Künstlicher Intelligenz im touristischen Kontext seitens der deutschsprachigen Bevölkerung auf Basis des Artificially Intelligent Device Use Acceptance (AIDUA)-Modells - Kathrin John; Verena Fischer; Valentin Mayer (Standort, 2026)

Schizolepidopsis gerrienneii sp. nov.: an early jurassic ovulate cone from Belgium - Léa De Brito; Valentin Fischer; Pascal Godefroit; Cyrille Prestianni (Plant Systematics and Evolution, 2026)

Taken to extremes: Loss of plastid rpl32 in Streptophyta and Cuscuta’s unconventional solution for its replacement - Karsten Fischer; Sondre Valentin Jordbræk; Stian Olsen; Mathias Bockwoldt; Rainer Schwacke; Björn Usadel; Kirsten Krause (Molecular Phylogenetics and Evolution, 2025)

Ecological restoration and biodiversity-friendly management of urban grasslands – A global review on the current state of knowledge - Réka Fekete; Orsolya Valkó; Leonie K. Fischer; Balázs Deák; Valentin H. Klaus (Journal of Environmental Management, 2024)

Identifying the optimal landscape configuration for landscape multifunctionality - Andrea Larissa Boesing; Valentin H. Klaus; Margot Neyret; Gaëtane Le Provost; Sophie Peter; Markus Fischer; Peter Manning (Ecosystem Services, 2024)

Establishment of Arthrobotrys flagrans as biocontrol agent against the root pathogenic nematode Xiphinema index - Valentin Wernet; Reinhard Fischer (Environmental Microbiology, 2023)
Plant‐parasitic nematodes cause devastating agricultural damage worldwide. Only a few synthetic nematicides can be used and their application is limited in fields. Therefore, there is a need for sustainable and environment‐friendly alternatives. Nematode‐trapping fungi (NTF) are natural predators of nematodes. They capture and digest them with their hyphae and are starting to being used as bio‐control agents. In this study, we applied the NTF Arthrobotrys flagrans ( Duddingtonia flagrans ) against the wine pathogenic nematode Xiphinema index . A. flagrans reduced the number of X. index juveniles in pot cultures of Ficus carica , an alternative host plant for X. index , significantly. Sodium‐alginate pellets with A. flagrans spores were produced for vineyard soil inoculation under laboratory conditions. The NTF A. conoides , A. musiformis and A. superba were enriched from several soil samples, showing their natural presence. Trap formation is an energy‐consuming process and depends upon various biotic and abiotic stimuli. Here, we show that bacteria of the genus Delftia , Bacillus , Pseudomonas , Enterobacter and Serratia induced trap formation in NTF like A. conoides and A. oligospora but not in A. flagrans in the absence of nematodes. The application of NTF along with such bacteria could be a combinatorial way of efficient biocontrol in nematode‐infested soil.

Drivers of soil respiration across a management intensity gradient in temperate grasslands under drought - Antonios Apostolakis; Ingo Schöning; Beate Michalzik; Valentin H. Klaus; Runa S. Boeddinghaus; Ellen Kandeler; Sven Marhan; Ralph Bolliger; Markus Fischer; Daniel Prati; Falk Hänsel; Thomas Nauss; et al. (Nutrient Cycling in Agroecosystems, 2022)
Soil respiration is an important pathway of soil organic carbon losses in temperate grasslands; however, it is rarely studied across broad management intensity gradients in a landscape. Using the soda-lime method, we measured in-situ soil CO 2 efflux with single measurements of long exposure time (i.e. 3 day long) in 150 grasslands in three German regions in early summer 2018 and 2019. The grasslands ranged from unfertilized and grazed grasslands to intensively fertilized and frequently harvested ones. To assess effects of grazing and fertilization intensities and plant diversity on soil CO 2 efflux, we used Structural Equation Modeling to account for direct effects and indirect effects through soil and plant organic matter quantity and quality. Soil CO 2 efflux was suppressed by limited water availability caused by naturally occurring droughts in both study years. Under the prevailing environmental conditions, grazing intensity, plant biomass and plant C:N ratio were not related to soil CO 2 efflux. In contrast, fertilization intensity was positively associated with soil CO 2 efflux (standardized coefficient of net effect: + 0.04 in 2018 and + 0.03 in 2019). This was because fertilization led to lower plant species richness and, thus, to lower C:N ratios in soils, which were associated with higher soil CO 2 efflux (plant species richness net effect: −0.09 in 2018 and −0.18 in 2019; soil C:N ratio direct effect: −0.23 in 2018 and −0.33 in 2019). Intensively managed grasslands have higher soil respiration than extensively managed, plant species-rich grasslands even under the extreme conditions of natural droughts.

Direct and plant community mediated effects of management intensity on annual nutrient leaching risk in temperate grasslands - Antonios Apostolakis; Ingo Schöning; Valentin H. Klaus; Beate Michalzik; Wolf-Anno Bischoff; Runa S. Boeddinghaus; Ralph Bolliger; Markus Fischer; Norbert Hölzel; Ellen Kandeler; Till Kleinebecker; Peter Manning; et al. (Nutrient Cycling in Agroecosystems, 2022)
Grassland management intensity influences nutrient cycling both directly, by changing nutrient inputs and outputs from the ecosystem, and indirectly, by altering the nutrient content, and the diversity and functional composition of plant and microbial communities. However, the relative importance of these direct and indirect processes for the leaching of multiple nutrients is poorly studied. We measured the annual leaching of nitrate, ammonium, phosphate and sulphate at a depth of 10 cm in 150 temperate managed grasslands using a resin method. Using Structural Equation Modeling, we distinguished between various direct and indirect effects of management intensity (i.e. grazing and fertilization) on nutrient leaching. We found that management intensity was positively associated with nitrate, ammonium and phosphate leaching risk both directly (i.e. via increased nutrient inputs) and indirectly, by changing the stoichiometry of soils, plants and microbes. In contrast, sulphate leaching risk was negatively associated with management intensity, presumably due to increased outputs with mowing and grazing. In addition, management intensification shifted plant communities towards an exploitative functional composition (characterized by high tissue turnover rates) and, thus, further promoted the leaching risk of inorganic nitrogen. Plant species richness was associated with lower inorganic nitrogen leaching risk, but most of its effects were mediated by stoichiometry and plant community functional traits. Maintaining and restoring diverse plant communities may therefore mitigate the increased leaching risk that management intensity imposes upon grasslands.

Räuberische Pilze mit Anwendungspotenzial - Valentin Wernet; Nicole Wernet; Reinhard Fischer (BIOspektrum, 2021)
Nematode-trapping fungi, such as Duddingtonia flagrans , are fascinating carnivorous microorganisms. In a nutrient-rich environment they live as saprotrophs, but if nutrients are scarce and in the presence of nematodes, they can switch to a predatory lifestyle. The switch is characterized by the formation of complex, adhesive trap structures. The interaction requires a sophisticated interspecies communication with pheromones, secondary metabolites, and virulence factors.

Morphometric Analysis of the Mandible of Primitive Sabertoothed Felids from the late Miocene of Spain - Narimane Chatar; Valentin Fischer; Gema Siliceo; Mauricio Antón; Jorge Morales; Manuel J. Salesa (Journal of Mammalian Evolution, 2021)

New cell lines for efficient propagation of koi herpesvirus and infectious salmon anaemia virus - Valentin Eckart; Takuya Yamaguchi; Kati Franzke; Sven M. Bergmann; Pierre Boudinot; Edwige Quillet; Motokazu Kawanobe; Neila Alvarez de Haro; Uwe Fischer (Journal of Fish Diseases, 2019)
The production of piscine viruses, in particular of koi herpesvirus (KHV, CyHV‐3) and infectious salmon anaemia virus (ISAV), is still challenging due to the limited susceptibility of available cell lines to these viruses. A number of cell lines from different fish species were compared to standard diagnostic cell lines for KHV and ISAV regarding their capability to exhibit a cytopathic effect (CPE) and to accumulate virus. Two cell lines, so far undescribed, appeared to be useful for diagnostic purposes. Fr994, a cell line derived from ovaries of rainbow trout ( Oncorhynchus mykiss ), produced constantly high ISA virus (ISAV) titres and developed a pronounced CPE even at high cell passage numbers, while standard cell lines are reported to gradually loose these properties upon propagation. Another cell line isolated from the head kidney of common carp ( Cyprinus carpio ), KoK, showed a KHV induced CPE earlier than the standard cell line used for diagnostics. A third cell line, named Fin‐4, established from the fin epithelium of rainbow trout did not promote efficient replication of tested viruses, but showed antigen sampling properties and might be useful as an in vitro model for virus uptake or phagocytosis.

Land use intensity, rather than plant species richness, affects the leaching risk of multiple nutrients from permanent grasslands - Valentin H. Klaus; Till Kleinebecker; Verena Busch; Markus Fischer; Norbert Hölzel; Sascha Nowak; Daniel Prati; Deborah Schäfer; Ingo Schöning; Marion Schrumpf; Ute Hamer (Global Change Biology, 2018)
The intensification of land use constitutes one of the main drivers of global change and alters nutrient fluxes on all spatial scales, causing landscape‐level eutrophication and contamination of natural resources. Changes in soil nutrient concentrations are thus indicative for crucial environmental issues associated with intensive land use. We measured concentrations of NO 3 –N, NH 4 –N, P, K, Mg, and Ca using 1,326 ion‐exchange resin bags buried in 20 cm depth beneath the main root zone in 150 temperate grasslands. Nutrient concentrations were related to land use intensity, that is, fertilization, mowing, grazing intensities, and plant diversity by structural equation modeling. Furthermore, we assessed the response of soil nutrients to mechanical sward disturbance and subsequent reseeding, a common practice for grassland renewal. Land use intensity, especially fertilization, significantly increased the concentrations of NO 3 –N, NH 4 –N, K, P, and also Mg. Besides fertilization (and tightly correlated mowing) intensity, grazing strongly increased NO 3 –N and K concentrations. Plant species richness decreased P and NO 3 –N concentrations in soil when grassland productivity of the actual year was statistically taken into account, but not when long‐term averages of productivity were used. Thus, we assume that, in the actual study year, a distinct drought period might have caused the observed decoupling of productivity from fertilization and soil nutrients. Breaking up the grassland sward drastically increased NO 3 –N concentrations (+146%) but reduced NH 4 –N, P, and K concentrations, unbalancing soil nutrient stoichiometry and boosting the risk of N leaching. Reseeding the sward after disturbance did not have a short‐term effect on nutrient concentrations. We conclude that renewal of permanent grassland should be avoided as far as possible and future grassland management has to strongly rise the effectiveness of fertilization. Additionally, grassland management might have to increasingly taking care of periods of drought, in which nutrient additions might not increase plant growth but potentially only facilitate leaching.

Land use intensification alters ecosystem multifunctionality via loss of biodiversity and changes to functional composition - Eric Allan; Pete Manning; Fabian Alt; Julia Binkenstein; Stefan Blaser; Nico Blüthgen; Stefan Böhm; Fabrice Grassein; Norbert Hölzel; Valentin H. Klaus; Till Kleinebecker; E. Kathryn Morris; et al. (Ecology Letters, 2015)
Global change, especially land‐use intensification, affects human well‐being by impacting the delivery of multiple ecosystem services (multifunctionality). However, whether biodiversity loss is a major component of global change effects on multifunctionality in real‐world ecosystems, as in experimental ones, remains unclear. Therefore, we assessed biodiversity, functional composition and 14 ecosystem services on 150 agricultural grasslands differing in land‐use intensity. We also introduce five multifunctionality measures in which ecosystem services were weighted according to realistic land‐use objectives. We found that indirect land‐use effects, i.e. those mediated by biodiversity loss and by changes to functional composition, were as strong as direct effects on average. Their strength varied with land‐use objectives and regional context. Biodiversity loss explained indirect effects in a region of intermediate productivity and was most damaging when land‐use objectives favoured supporting and cultural services. In contrast, functional composition shifts, towards fast‐growing plant species, strongly increased provisioning services in more inherently unproductive grasslands.

Grassland management intensification weakens the associations among the diversities of multiple plant and animal taxa - Pete Manning; Martin M. Gossner; Oliver Bossdorf; Eric Allan; Yuan-Ye Zhang; Daniel Prati; Nico Blüthgen; Steffen Boch; Stefan Böhm; Carmen Börschig; Norbert Hölzel; Kirsten Jung; et al. (Ecology, 2015)
Land‐use intensification is a key driver of biodiversity change. However, little is known about how it alters relationships between the diversities of different taxonomic groups, which are often correlated due to shared environmental drivers and trophic interactions. Using data from 150 grassland sites, we examined how land‐use intensification (increased fertilization, higher livestock densities, and increased mowing frequency) altered correlations between the species richness of 15 plant, invertebrate, and vertebrate taxa. We found that 54% of pairwise correlations between taxonomic groups were significant and positive among all grasslands, while only one was negative. Higher land‐use intensity substantially weakened these correlations (35% decrease in r and 43% fewer significant pairwise correlations at high intensity), a pattern which may emerge as a result of biodiversity declines and the breakdown of specialized relationships in these conditions. Nevertheless, some groups (Coleoptera, Heteroptera, Hymenoptera and Orthoptera) were consistently correlated with multidiversity, an aggregate measure of total biodiversity comprised of the standardized diversities of multiple taxa, at both high and low land‐use intensity. The form of intensification was also important; increased fertilization and mowing frequency typically weakened plant–plant and plant–primary consumer correlations, whereas grazing intensification did not. This may reflect decreased habitat heterogeneity under mowing and fertilization and increased habitat heterogeneity under grazing. While these results urge caution in using certain taxonomic groups to monitor impacts of agricultural management on biodiversity, they also suggest that the diversities of some groups are reasonably robust indicators of total biodiversity across a range of conditions.

Ichthyosaurs from the French Rhaetian indicate a severe turnover across the Triassic–Jurassic boundary - Valentin Fischer; Henri Cappetta; Peggy Vincent; Géraldine Garcia; Stijn Goolaerts; Jeremy E. Martin; Daniel Roggero; Xavier Valentin (The Science of Nature, 2014)

Increased Cation Conductance in Human Erythrocytes Artificially Aged by Glycation - Yuliya V. Kucherenko; Shefalee K. Bhavsar; Valentin I. Grischenko; Uwe R. Fischer; Stephan M. Huber; Florian Lang (The Journal of Membrane Biology, 2010)